Surface functionalization of nanocellulose with polyethyleneimine and magnetic nanoparticles for efficient removal of anionic dye in wastewater - Mubarak, Asmaa Ali; Ilyas, R.A.; Ngadi, Norzita; Nordin, Abu Hassan; Alkbir, M.F.M. (Elsevier B.V., 2025)
This study presents a novel adsorbent, MNCPEI, synthesized through a simple and efficient process for the effective removal of anionic dyes. MNCPEI was developed by crosslinking nanocellulose with polyethyleneimine (PEI) and incorporating magnetic nanoparticles (MNP). Key synthesis parameters, including the ratios of nanocellulose, PEI, and MNP, as well as impregnation time and crosslinking degree, were systematically optimized to enhance the adsorbent's characteristics and synthesis efficiency. Optimal conditions for MNCPEI synthesis were determined, with the nanocellulose-to-PEI ratio of 1:2 and MNP dosage of 0.6 g demonstrating superior adsorption capacity for the anionic dye Reactive Black 5 (RB5). This aligns with literature findings emphasizing the critical role of material ratios in improving adsorption performance. FTIR analysis and acid-base titration confirmed the surface functionalization of nanocellulose with PEI and MNP, highlighting the effectiveness of these modifications in enhancing dye removal efficiency. The performance of MNCPEI was systematically evaluated under varying experimental conditions, including contact time (0–180 min), adsorbent dosage (0.05–2.0 g), initial dye concentration (0.025–0.3 g/L), pH (2–9), and temperature (25–70 °C). The results showed that RB5 attached using a chemisorption process, similar to what has been found in other functionalized nanomaterial systems. MNCPEI was also very reusable, keeping its high adsorption efficiency through four regeneration cycles. This demonstrated its potential for long-term wastewater treatment.